Dalung Bojong in The Construction of a Hierarchical System of Regulations - Murdiana, Elfa; Rodliyah, Nunung; Wijayati, Mufliha; Oktora, Nency Della (Journal Research of Social Science, Economics, and Management, 2024)
This article describes the elements arranged in the Bojong dalung inscription born in the XVI-XVII centuries. By using the study of legal texts on the Dalung Bojong Inscription and the study of concepts in legal science, a hierarchy of regulatory systems in the form of values, principles, and legal acts was found. Values are the basis for the birth of principles and principles are the basis for the birth of legal acts explicitly contained in eleven articles. The values of divinity, humanity, nationality, democracy, and justice are the basis of values that give birth to the consensualist principle, the principle of equality, the principle of protection, the principle of legal certainty, the principle of territoriality, and the principle of personality. These six principles became the basis for the birth of legal acts in the form of Participation (Article 5), Crimes Against the Body; Quarreling or fighting among people (article 2), Inciting a struggle (article 3), Crimes against property; theft by force/robbery (article 4), theft (article 10) and Crimes of disturbing public safety; Article 6,7 and Article 10 on gambling, drinking intoxicating beverages.